2018
DOI: 10.1038/s41467-018-06473-x
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of effects of exclusive breastfeeding on infant gut microbiota across populations

Abstract: Previous studies on the differences in gut microbiota between exclusively breastfed (EBF) and non-EBF infants have provided highly variable results. Here we perform a meta-analysis of seven microbiome studies (1825 stool samples from 684 infants) to compare the gut microbiota of non-EBF and EBF infants across populations. In the first 6 months of life, gut bacterial diversity, microbiota age, relative abundances of Bacteroidetes and Firmicutes, and predicted microbial pathways related to carbohydrate metabolis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
268
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 338 publications
(302 citation statements)
references
References 61 publications
13
268
0
5
Order By: Relevance
“…Newborns fed with mother's breast milk have a higher abundance of beneficial bacteria species compared to formula-fed children. Breastfeeding is associated with favorable alteration of infant GM (high colonization with Bifidobacterium and Lactobacillus, Staphylococcus and Bacteroides, low colonization with Clostridium, Escherichia), in addition to inhibiting colonization by potential pathogens (Escherichia coli, Helicobacter jejuni, Shigella, Vibrio cholera, Salmonella), as described in several previous studies [25][26][27]. In comparison, formula-fed infants are enriched in functions typical of the adult microbiota and have higher counts of Clostridia (C. paraputrificum, C. perfringens, C. clostridiiforme, C. difficile, and C. tertium), Streptococcus (S. bovis, S. faecalis, and S. faecium), and Proteobacteria (Enterobacter cloacae, Citrobacter spp., and Bilophila wadsworthia) than do breast-fed infants, and with delayed colonization by Bifidobacteria [22].…”
Section: Introductionmentioning
confidence: 82%
“…Newborns fed with mother's breast milk have a higher abundance of beneficial bacteria species compared to formula-fed children. Breastfeeding is associated with favorable alteration of infant GM (high colonization with Bifidobacterium and Lactobacillus, Staphylococcus and Bacteroides, low colonization with Clostridium, Escherichia), in addition to inhibiting colonization by potential pathogens (Escherichia coli, Helicobacter jejuni, Shigella, Vibrio cholera, Salmonella), as described in several previous studies [25][26][27]. In comparison, formula-fed infants are enriched in functions typical of the adult microbiota and have higher counts of Clostridia (C. paraputrificum, C. perfringens, C. clostridiiforme, C. difficile, and C. tertium), Streptococcus (S. bovis, S. faecalis, and S. faecium), and Proteobacteria (Enterobacter cloacae, Citrobacter spp., and Bilophila wadsworthia) than do breast-fed infants, and with delayed colonization by Bifidobacteria [22].…”
Section: Introductionmentioning
confidence: 82%
“…The process of breast feeding plays a critical role in development of the infant gut microbiome. The initial seeding of the infant gut in the first few months of life is necessary for infant immune development and overall health(2428) with breastfeeding exclusivity and percentage critically influencing the infant gut microbiome(19, 28). In our analysis, the breast milk and infant microbiomes are seeded through multiple pathways, though primarily from areolar skin and infant oral sites.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, the microbiota is known to convert food components that would otherwise be indigestible into products with nutritional or biological value (see Rowland et al, ; Sela & Mills, , for reviews on this topic, the latter in infants), and nutrition itself is a well‐established modulator of cognitive outcomes. Breastfeeding, a dietary factor that influences microbiota maturation (Ho et al, ), has long been purported to improve cognitive outcomes (Johnstone et al, ), although more recent data indicate that this effect is largely accounted for by confounding variables such as maternal intelligence or education levels (Walfisch et al, ). On the other hand, both specific nutrient deficiencies and low overall diet quality are associated with negative long‐term impacts on cognitive development (Freeman et al, ; Tandon et al, ), and nutritional interventions in vulnerable populations have been shown to improve cognitive outcomes during childhood (e.g., Freeman et al, ; Isaacs et al, ; Lucas et al, ).…”
Section: Digging Deeper Into Mechanism: Pathways For a Microbial Inflmentioning
confidence: 99%